Use of Schema Theory in the Teaching of English Reading Comprehension in Senior High School - Hu, Wankun (International Journal of Social Sciences and Public Administration, 2024)
This paper examines the use of schema theory in enhancing English reading comprehension in senior high school students. Schema theory, a cognitive psychology framework, emphasizes that readers’ prior knowledge and experiences play a crucial role in comprehending new information. This paper summarizes the basic viewpoints of schema theory and discusses its practical applications in English reading comprehension in senior high school. Research has shown that implementing schema theory not only benefits students’ language skills but also fosters their critical thinking abilities. When students are able to connect new information with their existing schemas, they become more familiar with analyzing and interpreting complex texts. This theory encourages active engagement with the material and promotes a deeper level of comprehension. This paper also addresses challenges and solutions in implementing schema theory. By incorporating schema theory into reading classes, teachers can help students develop a deeper understanding of texts, improve their reading efficiency, and enhance their overall English proficiency.